Comparison of Leaf Beetle (Coleoptera: Chrysomelidae) Diversity of Turkey and Neighboring Countries with Respect to Species Numbers and Endemicity - Ali Nafiz Ekiz (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
According to number of leaf beetle species andsubspecies, Turkey is the most diverse country by far among its neighbors with916 reported taxa. The species numbers of neighboring countries are as follows:Bulgaria 603, Ukraine 582, Greece 507, Romania 495, Iran 479, Russia (only thesouthern European part included) 441, Azerbaijan 373, Armenia 294, Georgia 273,Syria 254, Cyprus (whole island) 136, Iraq 120 and Moldova 103. As to number ofendemic taxa, Iran and Turkey keep ahead with 103 and 88 endemics respectively.The closest country is Greece with 32 endemics and Moldova contains no endemictaxa. However, when we calculate the rate of endemism, Iran is unmatched withan endemism ratio of 21.50%, followed by Iraq and Turkey having 10.00% and9.61% endemism ratios respectively. When we consider all countries (exceptRussia, because it is partly included in the current study), there is aninsignificant weak correlation between the number of species and the surfacearea of selected countries. Normally, under similar biogeographic conditions, alarger area should include more species, but all countries here are nor similarin terms of biogeography. In fact, the known species numbers of a region arealso greatly affected by the quantity and quality of relevant researchconducted in that area. Here, the case of Iran (and perhaps some othercountries) is most likely associated with the low number of research on leafbeetles. When we exclude Iran, there is a moderate positive correlation betweenthe species numbers and surface area.